El derecho a un ambiente sano y el funcionamiento de la planta de tratamiento de aguas residuales en el barrio “El Batan” en la cuidad de Ibarra (2023-2024) - Rocha Estévez, Alan Israel (2024)
In Ecuador, the right to a healthy environment is guaranteed by the Constitution, but its fulfillment depends on key infrastructure like wastewater treatment plants. The research aimed to analyze the compliance with the right to a healthy environment in the context of the operation of the wastewater treatment plant in the 'El Batán' neighborhood in the city of Ibarra during the 2023- 2024 period. Considering that the treatment plant faces challenges due to urban growth, impacting the quality of the local environment. The research used a mixed approach, combining document analysis and resident surveys. Data was collected on the treatment plant’s capacity and efficiency, compliance with environmental regulations, and community perceptions regarding environmental impacts. The results indicate that the right to a healthy environment in Ecuador, protected by the 2008 Constitution and the Organic Environmental Code, requires that wastewater treatment plants operate under strict environmental standards. In the case of the 'El Batán' plant in Ibarra, this study identifies the need to align with these principles, as community perceptions reflect concerns about unpleasant odors and constant noise, which compromise their quality of life. The Constitution recognizes in Article 14 the right to a balanced environment, while the Organic Environmental Code establishes specific standards for the management of effluents and sludge. These legal frameworks aim to ensure the sustainability and well-being of communities affected by industrial activities. The Sustainable Development Goals, particularly SDG 6, reinforce the obligation to improve water quality and ensure that wastewater treatment meets health and sustainability standards.